Community-based corrections : a text/reader - Barton-Bellessa, Shannon M.; Hanser, Robert D. (Thousand Oaks, California : SAGE, 2012)
Presenting a practical viewpoint for the course, this book offers a textbook/reader alternative to the traditional textbook format. The book is divided into 11 author-written sections that present basic concepts, key terms, and recent data. Each section is followed by two to three research-based articles. The authors' expertise in special needs populations and the comparative field gives the book a unique perspective. Key features include: Photos, tables, charts, and graphs that provide valuable visual support; Article introductions and review questions to help focus on the key aspects of each article; the text/reader format provides students with core theories and concepts, followed by carefully selected, edited articles that have previously appeared in a number of leading criminal justice academic journals.
1. History and development of community-based corrections -- 2. Pretrial release and diversion -- 3. Restorative justice -- 4. The viability of treatment perspectives -- 5. Assessment and risk prediction -- 6. Probation management and case planning -- 7. Community-based residential intermediate sanctions -- 8. Community-based nonresidential and economic intermediate sanctions -- 9. Parole management, case planning, and reentry -- 10. Juvenile offenders -- 11. Specialized and problematic offender typologies in a changing era
Includes bibliographical references (p. 608-614) and index
Keywords: Community-based corrections; Criminals -- Rehabilitation